Inventory of household goods in a dowry for Maria Van Doren - Van Deventer, James
Inventory (1829 June 20) compiled by Van Deventer of household goods provided by Jacob Van Doren as a dowry for his daughter, Maria Van Doren, and held in trust by Van Deventer until his marriage to her.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Van Deventer, Maria Van Doren, -- active 1829.; Van Doren, Jacob, -- active 1829.; Dowry -- United States -- 19th century